Potensi Pupuk Organik Cair Asal Limbah Organik Sebagai Bahan Dasar Formulasi Agens Hayati Terhadap Xanthomonas oryzae dan Pyricularia oryzae Penyakit Tanaman Padi - Deli Annisa Virca (Fakultas Pertanian, 2025)
Xanthomonas oryzae, which causes bacterial leaf blight (HDB), and Pyricularia oryzae, which causes blast disease, are major pathogens of rice in Indonesia. Excessive chemical control risks health and the environment, so environmentally friendly alternatives such as the application of biological control agents (APH) are needed. This study aimed to evaluate the viability and antagonistic effectiveness of three APH isolates (Bacillus subtilis JB12, Pseudomonas putida Pf10, and Trichoderma sp.) formulated in liquid organic fertilizer (POC) made from organic waste (vegetables, fruits, straw, and cow dung compost). The study used a completely randomized design (CRD) with three treatments and nine replications. Parameters observed included microbial viability, POC characteristics, and inhibition against pathogens. The results showed that the three APH were able to survive up to 10 weeks. The KS formulation produced the highest population of B. subtilis (2.05 × 10¹⁰ cfu/mL) and P. putida (2.08 × 10¹⁰ cfu/mL) at week 9, while the JE formulation produced the highest population of Trichoderma sp. (4.21 × 10⁸ cfu/mL). KS formulation gave the highest inhibition against X. oryzae with inhibition zone respectively: B. subtilis 10 mm, P. putida 5 mm, and Trichoderma sp. 5 mm. Against P. oryzae, SB formulation was most effective for B. subtilis (85%), KS formulation for P. putida (70%), and JE formulation for Trichoderma sp. (56.2%). Thus, the POC formulation made from organic waste has the following potential.
Reuploud file repositori 8 APr 2026_Firli_tata
Keywords: Liquid organic fertilizer; biological agents; viability; inhibition